The Spiritualist Movement: Speaking with the Dead in America and Around the World edited by Christopher M. Moreman - Gauld, Alan (Journal of Scientific Exploration, 2014)
<!–[if gte mso 9]> <![endif]–> The Spiritualist Movement is divided into three hardback volumes (handsomely produced) which between them contain 43 chapters on assorted aspects of the subject, the boundaries of which are generously interpreted. Most of the chapters are between 15 and 25 pages in length. The topics covered can be relatively narrow or relatively broad, and not all of them will be of keen interest to every reader. The contributors (who range from Ph.D. candidates to emeritus professors) are of varied academic backgrounds and attitudes toward the phenomena or alleged phenomena of Spiritualism. Some are pretty skeptical, others less so-indeed (interestingly), several are or have been practicing mediums. However, excessive partisanship, pro or con, is refreshingly absent. The editor, Christopher Moreman, makes clear in his Introduction (which is printed in each of the three volumes) that his "collection" (he also refers to it as an "anthology") does not aim to provide a "comprehensive coverage of scholarship on Spiritualism," but rather to "illustrate the complexity of the movement and the ways it might be open to academic consideration." And this is the light in which we must consider it. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif"; –> <!–[endif] –>